Impact of Laser Remelting Parameters on the Microstructure and Properties of Sprayed Ni20Cr Coatings with Rhenium Addition - I. Kalemba-Rec; M. Kopyściański; P. Śliwiński; S. Dymek; M.S. Węglowski; A. Wrona; K. Groń (Archives of Metallurgy and Materials)
The study was focused on the characterization of microstructural evolution and microhardness in the plasma-sprayed and laser remelted Ni-Cr coatings with 20% addition of rhenium on stainless steel. The remelting process was performed with different laser power and laser traverse speed. The laser remelting process improves the quality of plasma sprayed Ni-Cr-Re coatings, reducing the porosity and the inhomogeneity of the chemical composition. The remelted coatings were characterized by a dendritic microstructure. Microsegregation of rhenium to dendrites was observed. The remelted coatings have an iron content of over 40%, which is the result of too deep remelting with the substrate material. The iron content in the remelted coatings increases with the decrease in laser speed, but the rhenium content decreases. All tested coatings were characterized by hardness similar to that of the substrate material.